2017
DOI: 10.3390/catal7100283
|View full text |Cite
|
Sign up to set email alerts
|

Reactive Magnetron Sputter Deposition of Bismuth Tungstate Coatings for Water Treatment Applications under Natural Sunlight

Abstract: Bismuth complex oxides, in particular, bismuth tungstate, have recently attracted attention as promising photocatalytic materials for water treatment processes. In the present work, photocatalytic bismuth tungstate films were prepared by pulsed direct current (DC) reactive magnetron sputtering of Bi and W targets in an Ar/O 2 atmosphere onto spherically-shaped glass beads. The uniform coverage of the substrate was enabled by the use of oscillating bowl placed underneath the magnetrons. The atomic ratio of Bi/W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 36 publications
2
24
0
Order By: Relevance
“…The method provides such obvious advantages, in comparison to chemical methods, as; no requirement for toxic or hazardous precursors, an absence of hazardous process by-products, excellent control over uniformity and composition and great up-scaling potential. Despite the fact that magnetron sputtering is typically used for deposition of coatings onto flat substrates, the authors of the present paper have recently shown that it can be readily used for deposition of functional coatings onto particulates of various shapes and sizes, from several millimeters in diameter [4], to nanoparticulates [4,32].…”
Section: Introductionmentioning
confidence: 85%
See 3 more Smart Citations
“…The method provides such obvious advantages, in comparison to chemical methods, as; no requirement for toxic or hazardous precursors, an absence of hazardous process by-products, excellent control over uniformity and composition and great up-scaling potential. Despite the fact that magnetron sputtering is typically used for deposition of coatings onto flat substrates, the authors of the present paper have recently shown that it can be readily used for deposition of functional coatings onto particulates of various shapes and sizes, from several millimeters in diameter [4], to nanoparticulates [4,32].…”
Section: Introductionmentioning
confidence: 85%
“…Bismuth-oxide coatings were deposited in a one-step process in an arrangement similar to the one described in detail earlier [4,35]. In brief, the vacuum coating system includes two planar 300 × 100 mm 2 unbalanced type II magnetrons installed on the top of the vacuum chamber in a closed field, sputter-down configuration.…”
Section: Deposition Processmentioning
confidence: 99%
See 2 more Smart Citations
“…The production of crystalline layers or particles can be carried out by different processes, such as physical vapor deposition (PVD) [15], chemical vapor deposition (CVD) [16], magnetron sputtering [17,18] and a hydrothermal process [19]. The production of nonstoichiometric bismuth oxide presents a challenge.…”
Section: Introductionmentioning
confidence: 99%